Safety design of Experimental Plasma Generation Systems. (May 2017) - Bondarenko, Daniel; A. Gabbar, Hossam; Stoute, C.A. Barry
Abstract: The Experimental Plasma Generation System (EPGS) is a system proposed for studying and investigating the plasma behavior in vacuum conditions and under the influence of the varying boundary conditions. Such device is intended to verify the computational models with the physical data and to gauge on possible sources of risk. The design of EPGS and the associated safety risks are purposed to encompass a variety of existing plasma devices and to act as a case study for researchers interested in preventing risks in their plasma devices. The safety design of EPGS takes into consideration the target safety system design, input and output parameters, diagnostics, as well as the fault propagation scenarios with respect to the Process Safety Management (PSM) via the IEC 61508 standard. The process to the design, the initial findings in the simulation and the experiment point to primary dangers of dealing with high voltages (HV) and vacuum devices, as well as the electromagnetic interference. The cumulative outcome of the current work is to provide groundwork for safety design of plasma devices that will have scalable properties in both the physical and the safety parameters. Highlights: Engineering design of proposed experiment of plasma generation system (EPGS). Safety analysis of EPGS. Apply IEC61508 on safety design of plasma devices. Simulation of EPGS safety system using Simulink. Virtual Simulation and Experimental verification of plasma generation case study.